60.0k views
1 vote
Identify a possible first step using the elimination method to solve the system and then find the solution to the system. 3x - 5y = -2 2x + y = 3 A) Multiply first equation by -3 and second equation by 2, solution (1, 1). B) Multiply first equation by -2 and second equation by 3, solution (1, 1). Eliminate C) Multiply first equation by -3 and second equation by 2, solution (1, -1). D) Multiply first equation by -2 and second equation by 3, solution (1, -1)

2 Answers

0 votes

Answer:

It's B

Explanation:

I did it on UsaTestprep

2 votes

ans is b...multiply eqn 1 by -2 and eqn 2 by 3

=》 -6x + 10y = 4...eqn 3

=》 6x + 3y = 9...eqn 4

add eqn 3 and 4...

=》13y = 13

=》y =1 and x = 1

User Shonia
by
5.1k points